Multiparametric Intraoperative Ultrasound in Oncological Neurosurgery: A Pictorial Essay - Prada, Francesco; Ciocca, Riccardo; Corradino, Nicoletta; Gionso, Matteo; Raspagliesi, Luca; Vetrano, Ignazio Gaspare; Doniselli, Fabio; Del Bene, Massimiliano; DiMeco, Francesco (Frontiers in Neuroscience, 2022)
Intraoperative ultrasound (ioUS) is increasingly used in current neurosurgical practice. This is mainly explained by its affordability, handiness, multimodal real-time nature and overall by its image spatial and temporal resolution. Identification of lesion and potential residue, analysis of the vascularization pattern and characterization of the nature of the mass are only some of the advantages that ioUS offers to guide safe and efficient tumor resection. Technological advances in ioUS allows to achieve both structural and functional imaging. B-mode provides high resolution visualization of the lesion and of its boundaries and relationships. Pioneering modes such as contrast-enhanced ultrasound (CEUS), ultrasensitive doppler and elastosonography are tools with great potential in characterizing different functional aspects of the lesion in both a qualitative and quantitative manner. As already happening for many organs and pathologies the combined use of different US modalities offers new insights in a multiparametric fashion. Herein, we present the potential of our multiparametric approach for ioUS during neuro-oncological surgery. In this effort, we provide a pictorial essay focusing on the most frequent pathologies: low- and high- grade gliomas, meningiomas and brain metastases.